Circulating PD1+Vδ1+γδ T Cell Predicts Fertility in Endometrial Polyp Patients of Reproductive-Age - Li, Xiao-Hong; Lu, Mei-Yin; Li, Yi-jia; Liu, Zong-hua; Yin, Zhi-nan; Liu, Bin; Wu, Yang-zhe (Frontiers in Immunology, 2021)
Clinically, immune cell function is correlated with pathogenesis of endometrial polyp (EP) and infertility of women of reproductive-age. However, the underlying immune cell hallmark in EP patients remains unclear. Here, we focused on analyzing circulating immune cells, and attempted to reveal the correlation between peripheral immune cell functional phenotypes and fertility in EP patients. Through comparison of circulating CD4+/CD8+ T cells, NK cells, and γδ T cells between 64 EP patients and 68 healthy females, we found that γδ T cells, but not CD4+/CD8+ T cells and NK cells, were immunologically correlated with conception rate and conception interval time. Specifically, total γδ T cells and the Vδ1+PD1+ γδ T subpopulation decreased whereas the Vδ1/Vδ2 ratio increased in EP patients compared to healthy controls. Moreover, the patients with the higher Vδ1/Vδ2 ratio (median value equals 1.04) had a poorer fertility and longer interval time of conception (210 days versus 158 days for control). Meanwhile, higher Vδ1+PD1+ γδ T cell proportion (median equals 15.7) was positively correlative with both higher conception rate and shortened median conception interval time (130 days for Vδ1+PD1high group versus 194 days for Vδ1+PD1low group). Notably, in healthy controls, both Vδ1/Vδ2 ratio and Vδ1+PD1+ γδ T cell proportion correlated with pregnancy rate oppositely, comparing to EP patients. Together, our results suggested that imbalanced γδ T cell population occurred in EP patients, and that Vδ1/Vδ2 ratio and PD-1 expression of Vδ1+ γδ T cells could be potentially developed into valuable predictors for fertility in EP patients.